The Soft Power of Authenticity: Lao Ecotourism as Participatory Exclusion - Kleinod-Freudenberg, Michael (Journal of Political Sociology, 2025)
Ecotourism is uniquely situated within a key tension of the current “greening” of global capitalism – conservation vs development, which also defines the political ecology of late socialist Laos. Synthesizing the results of fieldwork on model ecotourism projects this paper argues that a fetishized notion of Authenticity takes on material force in ecotourism practice that works as a soft, i.e. inclusive form of power tending to reproduce the marginalization of rural populations. The paper traces the sources of this intricate complex of participatory exclusion, describes its workings and twisted outcomes, and considers ecotourism futures in rural Laos in the context of increasing integration into China’s sphere of influence as well as potential pathways for transformation.